2024
DOI: 10.1038/s41598-024-52561-y
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplexes in MTOR and induction of autophagy

Piyali Majumder,
Chinmayee Shukla,
Arjun Arya
et al.

Abstract: G-quadruplex (G4) structures have emerged as singular therapeutic targets for cancer and neurodegeneration. Autophagy, a crucial homeostatic mechanism of the cell, is often dysregulated in neurodegenerative diseases and cancers. We used QGRS mapper to identify 470 G4 sequences in MTOR, a key negative regulator of autophagy. We sought to identify a functional context by leveraging the effect of G4-targeting ligands on MTOR G4 sequences. The effect of Bis-4,3, a G4 selective dimeric carbocyanine dye, was compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…As anticipated, the possibility of targeting cancer cells through the pharmacological stabilization of naturally occurring G4 structures has long been considered by chemists, physicists, biologists, and clinicians as an opportunity for developing molecules that are able to selectively counteract tumor formation and progression. In agreement with this, the number of G4 ligands has significantly grown over the last 25 years, constituting a superfamily of molecules, with up to 3000 different members to date, distinguished for their structure and biological activity (see Figure 3 for notable examples reported in the text) [ 21 , 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Limitations Of G4-based Antitumoral Therapiesmentioning
confidence: 84%
See 1 more Smart Citation
“…As anticipated, the possibility of targeting cancer cells through the pharmacological stabilization of naturally occurring G4 structures has long been considered by chemists, physicists, biologists, and clinicians as an opportunity for developing molecules that are able to selectively counteract tumor formation and progression. In agreement with this, the number of G4 ligands has significantly grown over the last 25 years, constituting a superfamily of molecules, with up to 3000 different members to date, distinguished for their structure and biological activity (see Figure 3 for notable examples reported in the text) [ 21 , 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Limitations Of G4-based Antitumoral Therapiesmentioning
confidence: 84%
“…At the functional level, the alteration of VEGF-R promotes an impairment of vascularization and, consequently, an inhibition of tumor growth and dissemination. Again, a recent study published by Majumder and colleagues demonstrated the capability of TMPyP4 to impair the expression of mTOR, a key factor in the autophagic process [ 23 ].…”
Section: Therapeutic Relevance Of G4 Structures In Cancermentioning
confidence: 99%